Kinase-dependent regulation of the secretion of thyrotrophin and luteinizing hormone by glucocorticoids and annexin 1 peptides. - John, C; Christian, H; Morris, J; Flower, R; Solito, E; Buckingham, J (2003)
Our previous studies have identified a role for annexin 1 (ANXA1), a protein produced by the pituitary folliculostellate cells, as a paracrine/juxtacrine mediator of the acute regulatory effects of glucocorticoids on the release of adrenocorticotropic hormone and other pituitary hormones. In the present study, we focused on the secretion of thyroid stimulating hormone (TSH) and luteinizing hormone (LH) and used a battery of ANXA1-derived peptides to identify the key domains in the ANXA1 molecule that are critical to the inhibition of peptide release. In addition, as ANXA1 is a substrate for protein kinase C (PKC) and tyrosine kinase, we examined the roles of these kinases in the manifestation of the ANXA1-dependent inhibitory actions of dexamethasone on TSH and LH release. Dexamethasone suppressed the forskolin-induced release of TSH and LH from rat anterior pituitary tissue in vitro. Its effects were mimicked by human recombinant ANXA1 (hrANXA1) and a truncated protein, ANXA1(1-188). ANXA1(Ac2-26), also suppressed stimulated peptide release but it lacked both the potency and the efficacy of the parent protein. Shorter N-terminal ANXA1 sequences were without effect. The PKC inhibitor PKC(19-36) abolished the inhibitory actions of dexamethasone on the forskolin-evoked release of TSH and LH; it also attenuated the inhibitory actions of ANXA1(Ac2-26). Similar effects were produced by annexin 5 (ANXA5) which sequesters PKC in other systems. By contrast, the tyrosine kinase inhibitors, p60v-src (137-157) and genistein, had no effect on the secretion of TSH or LH alone or in the presence of forskolin and/or dexamethasone. Dexamethasone caused the translocation of a tyrosine-phosphorylated species of ANXA1 to the surface of pituitary cells. The total amount of ANXA1 exported from the cells in response to the steroid was unaffected by tyrosine kinase blockade. However, the degree of tyrosine-phosphorylation of the exported protein was markedly reduced by genistein. These results suggest that (i) the ANXA1-dependent inhibitory actions of dexamethasone on the release of TSH and LH require PKC and sequences in the N-terminal domain of ANXA1, but are independent of tyrosine kinase, and (ii) while dexamethasone induces the cellular exportation of a tyrosine-phosphorylated species of ANXA1, tyrosine phosphorylation per se is not critical to the steroid-induced passage of ANXA1 across the membrane.